Palliative care need among inpatients in acute general hospitals in Nepal: a point prevalence survey - Acharya, Paras; Pandey, Bimal; Pokhrel, Yagya; Baral, Kedar; Munday, Dan; Gongal, Rajesh (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Developing palliative care services in acute hospitals is important to address the need of patients dying from malignant and non-malignant diseases. This study is carried out to assess the need of palliative care in Patan Hospital to inform the planning process for starting palliative care services. Methods: A cross-sectional, point prevalence survey of in-patient beds occupied in Patan Hospital was carried out using Supportive and Palliative Care Indicators Tool. For patients who met the criteria, symptom burden was noted. Results: Of the 116 patients admitted on the day of surveillance, 30% met the criteria for palliative care need; 60% were aged 60 or above. The most common conditions requiring palliative care need was lung disease (46%) followed by cardio vascular (23%) and neurological diseases (23%). The most common symptoms patients were suffering from were fatigue (60%) followed by shortness of breath (51%), inability to move (35%), abdominal distension (31%), anorexia (31%) and pain (25%). Conclusions: Almost one third of patients admitted to Patan Hospital need palliative care with majority of them being above sixty years. This highlights the need to develop palliative care services in the hospital to address the need of such patients and families to improve the quality of life in the last years of life.